2012
DOI: 10.1007/s00592-012-0426-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of normalization of fasting glucose by intensified insulin therapy and influence of eNOS polymorphisms on the incidence of restenosis after peripheral angioplasty in patients with type 2 diabetes: a randomized, open-label clinical trial

Abstract: Primary objective was to evaluate whether an intensified insulin therapy (IIT) incorporating the target of normal fasting glucose and HbA1c levels could halve the incidence of restenosis/amputation/SCA/death at 6 months after peripheral angioplasty compared with standard care (SC) in patients with type 2 diabetes (DMT2) affected by critical limb ischemia (CLI). Forty-six consecutive patients with DMT2 and CLI were randomly assigned to a parallel, open-label study with IIT (basal-bolus glulisine + glargine admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Indeed, it is well known that a decrease in the HbA1c level is usually achieved at the cost of higher risk of hypoglycemic episodes. These episodes are associated with increased mortality and decreased quality of life as shown in different cohorts T2DM patients [ 5 7 , 71 ]. Thus, reaching glycemic target without hypoglycemic events seems to bring particular benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is well known that a decrease in the HbA1c level is usually achieved at the cost of higher risk of hypoglycemic episodes. These episodes are associated with increased mortality and decreased quality of life as shown in different cohorts T2DM patients [ 5 7 , 71 ]. Thus, reaching glycemic target without hypoglycemic events seems to bring particular benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Basal insulin therapy with either glargine or detemir, as an add on to oral therapy of poorly controlled patients with T2DM, resulted in an increased concentration of cEPCs . Moreover, intensified insulin therapy with glargine and glulisine could further increase cEPC count compared with basal plus oral therapy in patients with T2DM and in critical limb ischemia …”
Section: Discussionmentioning
confidence: 99%
“…29 Moreover, intensified insulin therapy with glargine and glulisine could further increase cEPC count compared with basal plus oral therapy in patients with T2DM and in critical limb ischemia. 30 It has been shown in the MCF-7 breast cancer cell line that the inhibitory effect of metformin on cell proliferation was decreased when the expression of the AMPK subunit was inhibited by an siRNA. 31 In this study, we also showed a decrease in EPC proliferation from diabetic patients after treatment with metformin.…”
Section: Discussionmentioning
confidence: 99%
“…Intensive insulin therapy enhanced EPC counts over 6 months compared to basal-oral therapy (metformin and/or sulphonylureas) in patients with type 2 diabetes and peripheral artery disease undergoing peripheral angiography and subsequent angioplasty procedure. However, the cumulative incidence of restenosis/amputation/limb salvage procedures/death in patients with type 2 diabetes and chronic limb ischemia patients did not differ between groups at the study end, but there was a significant effect on eNOS gene variants [145]. In addition, hypoglycemia during insulin therapy may negatively impact EPC biology and clinical outcomes [56].…”
Section: Drug Class Mode Of Action Cardiovascular Effects Effects On ...mentioning
confidence: 98%
“…Insulin and insulin analogs binds to insulin receptors proven non-inferiority to standard therapy in CVOTs for newer insulin analogs detemir and glargin both increased EPC count (CD34+/VEGFR2+ and CD34+/VEGFR2+/CD133+) decreased adhesion molecules [143] no difference in CD34*/VEGFR2+ EPCs between groups receiving NPH insulin, insulin glargin, or oral therapy improved ECFC growth with NPH insulin and glargin decrease in intima media thickness [144] intensive insulin therapy increased EPC count (CD34+/VEGFR2+) no effect on clinical outcomes [145] reduced glucovariability by using insulin pumps increased the EPC count (CD34+/VEGFR+) compared to intensified insulin therapy Possible mechanisms of cardiovascular benefits include beneficial effects on EPC health. EPCs may benefit from improved glycemia and insulin sensitivity, enhanced nitric oxide production, reduced oxidative stress, and decreased inflammatory parameters.…”
Section: Drug Class Mode Of Action Cardiovascular Effects Effects On ...mentioning
confidence: 99%